Oscillation and Asymptotic Behavior of Three-Dimensional Third-Order Delay Systems - Ahmed Abdulhasan Naeif; Hussain Ali Mohamad (International Journal of Differential Equations)
In this paper, oscillation and asymptotic behavior of three-dimensional third-order delay systems are discussed. Some sufficient conditions are obtained to ensure that every solution of the system is either oscillatory or nonoscillatory and converges to zero or diverges as t goes to infinity. A special technique is adopted to include all possible cases for all nonoscillatory solutions (NOSs). The obtained results included illustrative examples.